Pengaruh Work Life Balance terhadap Kinerja Karyawan Generasi X dan Y di Jakarta - Angin, Irene Isabella Perangin; Saragih, Eva Hotnaidah (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2021)
The purpose of this research is to understanding the impact or work life balance on employee performance with the existence of X and Y in Jakarta. The dimensions of work life balance in this study was divided into four dimensions, personal life interference (PLIW), work interference personal life (WIPL), work enhancement personal life (WEPL) and personal life enhancement work (PLEW). This research was analyzing questionnaire’s result of 384 employees’ in Jakarta using quota sampling technique. The sample consist of 192 employee generation X and 192 employee generation Y. SPSS 23 was used for statistical analysis including regression. The partial test showed that WIPL has a insignificant effect on the performance of X and Y generation, PLIW has a negative and significant effect, WEPL and PLEW has a positive and significant effect. From the four dimensions of work life balance measurement, it was also founded that the variable that most influence generation X was PLEW and the variable that most influence generation Y was WEPL. Next research must pay attention to the measurement of employee performance with different methods, namely real measurement derived from company.